Immunosuppressors and immunomodulators in Neurology - Part I: a guide for management of patients underimmunotherapy - Abrantes, Fabiano Ferreira; Moraes, Marianna Pinheiro Moraes de; Albuquerque, José Marcos Vieira de, Filho; Alencar, Jéssica Monique Dias; Lopes, Alexandre Bussinger; Pinto, Wladimir Bocca Vieira de Rezende; Souza, Paulo Victor Sgobbi de; Oliveira, Enedina Maria Lobato de; Oliveira, Acary de Souza Bulle de; Pedroso, José Luiz; Barsottini, Orlando Graziani Povoas (Arquivos de Neuro-Psiquiatria, 2021)
For patients with autoimmune diseases, the risks and benefits of immunosuppressive or immunomodulatory treatment are a matter of continual concern. Knowledge of the follow-up routine for each drug is crucial, in order to attain better outcomes and avoid new disease activity or occurrence of adverse effects. To achieve control of autoimmune diseases, immunosuppressive and immunomodulatory drugs act on different pathways of the immune response. Knowledge of the mechanisms of action of these drugs and their recommended doses, adverse reactions and risks of infection and malignancy is essential for safe treatment. Each drug has a specific safety profile, and management should be adapted for different circumstances during the treatment. Primary prophylaxis for opportunistic infections and vaccination are indispensable steps during the treatment plan, given that these prevent potential severe infectious complications. General neurologists frequently prescribe immunosuppressive and immunomodulatory drugs, and awareness of the characteristics of each drug is crucial for treatment success. Implementation of a routine before, during and after use of these drugs avoids treatment-related complications and enables superior disease control.
Keywords: Immunosuppressive Agents; Immunologic Factors; Adrenal Cortex Hormones; Multiple Sclerosis; Autoimmune Diseases; Neurology